Asupan Zat Gizi dan Lamanya Menstruasi pada Kejadian Anemia Remaja Putri - Nurmita Rahmalina Aminy; Zulfiana Dewi (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2021)
Anemia in adolescent girls is still quite high. This is due to the blood loss caused by menstruation in adolescent girls every month and often consume fast food that has become a trend among adolescents is usually low of iron that will impact on decreased reproductive health, intelligence, learning concentration and growth process. The purpose of this study is to know the relationship between nutrient intake and duration of menstruation with the incidence of anemia in adolescent girls SMPN 4 Banjarbaru. The type of study is observational analytic with cross sectional design. The population are all students of class VII and VIII in SMPN 4 Banjarbaru in 2017. Samples are some of the population is 77 people determined by purposive sampling technique. Method of data collection using questionnaire and Food Recall 2 x 24 Hours. Analysis of data using statistical test of Rank Spearman Correlation Test with 90% confidence level. The result of this study that 64,9% energy intake of adolescent girls were classified as less, 80,5% protein intake were classified less, 97,4% of iron intake were classified less, 75,3% duration of menstruation on adolescent girls was normal and 54,5% classified as anemia. The results of statistical tests showed there is no correlation between energy and iron intake with the incidence of anemia on adolescent girls and there is a correlation between protein intake and duration of menstruation with incidence of anemia on adolescent girls. Suggestions for this study that staff of local health officials conduct the nutritional counseling about anemia in adolescent or activities of health promotion related to anemia so as to reduce the incidence of anemia in adolescent girls. Keywords: Anemia, Nutritional Intake, Duration Of Menstruation, Adolescent Literature: 71: 2006 - 2016